Dental Status of Children Below Age of Six Treated under General Anaesthesia over the Period of 2002-2004 - M. Kukletová; L. Pantuček; Z. Halačková; Z. Broukal; L. Izakovičová Hollá (Czech Dental Chamber, 2013)
Introduction: A proportion of preschool children with high caries experience (i.e. with early childhood caries, EEC) has been growing over the recent years in the Czech Republic and other countries. These high-risk children are often difficult to treat at standard dental office, especially if they have concomitant medical problems. The aim of the study was to evaluate dental status of preschool children referred to our department for treatment under general anaesthesia. Materials and Methods: In 2002-2004, totally 111 children below the age of six were referred for dental treatment under general anaesthesia (GA) to Dental clinic of the St. Ann's University Hospital Brno. Dental treatment has happened under standard conditions or under neuroleptanalgesia treatment in 53 children, 22 children were referred to Faculty Children Hospital. The remaining 31 children received treatment under general anaesthesia in our clinic, after unsuccessful attempts with other treatment options. Five children did not report to the treatment under GA. Based on their systemic conditions, these uncooperative children were divided into three groups: dental anxiety (DA), serious systemic conditions (SD) and other disabilities (OD). The following dental indicators were recorded: caries experience (dmft/DMFT) and restorative index (ri/RI). In addition, types of dental offices that referred children for treatment under general anaesthesia were recorded. The data were processed using descriptive statistics (Fisher exact test). Results: The mean age of all patients was 3.73 years, dmft = 5.55, out of which dt component = 5 = 5.23, mt = 0.19 and ft = 0.13, ri = 2.3%; DMFT = 0.19, out of which DT component = 0.19, MT+FT = 0.0 and RI = 0.0%; no significant differences among boys and girls were found. DA children - dmft = 5.29, dt = 4.9, mt = 0.29, ft = 0.1, ri = 2.38%. SD children - mean age 3.61, dmft = 7.57, dt = 7.29, mt = 0.0, ft = 0.29, ri = 3.17%. OD children - mean age 3.42, dmft =2.0, dt = 2.67, mt+ft = 0.0, ri = 0.0%. Statistically significant differences were only found between DA and SD group in the mean dmft values (p = 0.013) and mean dt values (0.009). Conclusion: The results of this study demonstrate that many uncooperative children can be successfully treated in standard dental office. In children treated under general anaesthesia, SD patients showed significantly higher mean dmft and lower ri than those with dental anxiety. In both groups, unfavourable dental indicators imply insufficient oral hygiene, but also poor dental attendance and inadequate follow-up.